III-V semiconductor extended short-wave infrared detectors - Savich, Gregory R.; Sidor, Daniel E.; Du, Xiaoyu; Wicks, Gary W.; Debnath, Mukul C.; Mishima, Tetsuya D.; Santos, Michael B.; Golding, Terry D.; Jain, Manish; Craig, Adam P.; Marshall, Andrew R. J. (Journal of vacuum science and technology. B, Nanotechnology & microelectronics, 2017)
The extended-shortwave infrared wavelength range, encompassing wavelengths from 2.2 to 3 μm, is significantly underdeveloped when compared to the shortwave and midwave infrared bands. Achieving high performance detectors in the extended-shortwave range is desirable; however, it is unclear whether to approach the wavelength range via the detector structures and materials common to the shortwave regime or those common to the midwave regime. Both approaches are studied here. Electrical and optical characteristics of conventional photodiodes and nBn architecture detectors with 2.8 μm cutoff wavelengths are analyzed for detectors with both lattice-mismatched InGaAs and lattice-matched InGaAsSb absorbing regions. Regardless of the absorber material, the nBn detectors show nearly 3 orders of magnitude improvements in performance over the conventional photodiode architecture, and the lattice-matched InGaAsSb nBn exhibits a further reduction in the dark current by more than an order of magnitude when compared to the lattice-mismatched InGaAs nBn. The InGaAsSb nBn exhibits high quality optical detection resulting in a high performance detector in the extended-shortwave infrared band.